Women's movements and the Filipina, 1986-2008 - Roces, Mina (Maria Natividad Roces) 1959-
This book is about a fundamental aspect of the feminist project in the Philippines: rethinking the Filipino woman. It focuses on how contemporary women's organizations have represented and refashioned the Filipina in their campaigns to improve women's status by locating her in history, society and politics; imagining her past, present and future; representing her in advocacy; and identifying strategies to transform her. The drive to alter the situation of women included a political aspect (lobbying and changing legislation) and a cultural one (modifying social attitudes and women’s own assessments of themselves). In this work Mina Roces examines the cultural side of the feminist agenda: how activists have critiqued Filipino womanhood and engaged in fashioning an alternative woman.